2023
DOI: 10.1038/s41598-023-37775-w
|View full text |Cite
|
Sign up to set email alerts
|

Developmental models of motor-evoked potential features by transcranial magnetic stimulation across age groups from childhood to adulthood

Abstract: To derive the maturation of neurophysiological processes from childhood to adulthood reflected by the change of motor-evoked potential (MEP) features. 38 participants were recruited from four groups (age mean in years [SD in months], number (males)): children (7.3 [4.2], 7(4)), preadolescents (10.3 [6.9], 10(5)), adolescents (15.3 [9.8], 11(5)), and adults (26.9 [46.2], 10(5)). The navigated transcranial magnetic stimulation was performed on both hemispheres at seven stimulation intensity (SI) levels from sub-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…A limitation of our study is the age and sex differences between groups in Experiment 1, given that both factors could influence MEP amplitudes. Research suggests that the effect of age on MEP amplitudes varied between muscles 61 63 . For instance, input–output curves of MEPs were different in the first dorsal interosseous but the same in the vastus lateralis between young and older adults 62 .…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our study is the age and sex differences between groups in Experiment 1, given that both factors could influence MEP amplitudes. Research suggests that the effect of age on MEP amplitudes varied between muscles 61 63 . For instance, input–output curves of MEPs were different in the first dorsal interosseous but the same in the vastus lateralis between young and older adults 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies which compared healthy younger participants with matched healthy older participants, have found both at rest and during contraction, older participants have smaller MEP amplitudes with longer latencies [28,29], the latter in keeping with the results of the current study. However, other studies have demonstrated that the effect of age on MEP amplitudes can vary between muscles [30][31][32]. One study, for example, showed inputoutput curves (stimulus intensity vs MEP amplitudes) of MEPs were different in an upper limb muscle, the first dorsal interosseous muscle, between younger and older adults but were the same for a lower limb muscle, vastus lateralis [31].…”
Section: Mep Amplitude and Latencymentioning
confidence: 99%